Świadomość rodziców na temat roli mediów w rozwoju mowy dziecka w wieku przedszkolnym - Błaszczyńska, Weronika; Troszczyńska, Dominika (Pedagogika Społeczna Nova, 2024)
Nowadays, the media play a significant role in human life. They make it easier to obtain information, provide entertainment, make everyday life easier and are part of it. Nowadays, children use them from an early age. The use of media influences a young person’s development, which, depending on many factors, may have both positive and negative effects. In the article, we present the development of a preschool child and the role that media can play in human life. We also present the results of research conducted on a group of 115 people, the aim of which was to examine parents’ opinions on the correlation between media use by a preschool child and the development of his or her speech.